Urban induced land use land cover changes in upper Deme watershed, Southwest Ethiopia - Kambo Dero; Wakshum Shiferaw; Biruk Zewde (Journal of Degraded and Mining Lands Management, 2021)
The study was aimed to assess urban induced land use land cover changes in the upper Deme watershed. Three satellite images of 1986, 2002, and 2019 were analyzed by ArcGIS and processed by supervised classification. Land use land cover change in the watershed increased for settlement, bare land, and croplands in the period 1986-2019 by 56.6%, 53%, and 0.25%, respectively. However, the land use land cover change in the watershed decreased for a water body, forest, and grassland by 65%, 57.7%, and 7%, respectively. These enforced to change the work habit and social bases. Out of converted lands, during 1986-2002, 34.9%, 53%, 18%, 40.9%, and 10.6% of bare land, cropland, forest land, grassland, and water bodies, respectively, in the upper Deme watershed were changed into settlement areas. During 2002-2019, 30.7%, 36.8%, 26.9%, 66%, and 33.3% of bare land, cropland, forest land, grassland, and water bodies, respectively, were changed into settlement areas. This shows urbanization results in a different change in economic, social, land use land cover, and watershed management activities in the upper Deme watershed.